UTILIZAÇÃO DE ÁLBUM SERIADO COMO ESTRATÉGIA DE EDUCAÇÃO/REEDUCAÇÃO ALIMENTAR PARA UM GRUPO DE HIPERTENSOS - Piasetzki, Cláudia T. d. R.; Hübner, Keila; Pauli, Patricia S.; Busnello, Maristela B.; Boff, Eva T. d. O. (Salão do Conhecimento, 2013)
Resumo